Functional investigation of neurodevelopmental effects of DISC1 and related psychosis risk genes - Bellini, Stefania (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Psychiatry, 2015)
Schizophrenia (SCZ) is a severe neurodevelopmental disorder, which affects about 1% of the population worldwide, and whose symptoms start during early adulthood. SCZ is determined by the interaction of genetic and environmental factors, but its pathophysiology is largely unknown. Heritability was estimated at 0.8: recent advances in genetics approaches have made it possible to identify a number of genetic variants associated to SCZ; however, most of them also increase the risk for other mental conditions. Thus, the functional investigation of penetrant risk genes for SCZ might better clarify pathophysiological mechanisms and provide a molecular profile of the disorder. In this work we focus on two risk genes: DISC1 and PAK7.
Keywords: Psychiatry, Ph.D.; Ph.D. Trinity College Dublin